2020
DOI: 10.1007/s11837-020-04441-9
|View full text |Cite
|
Sign up to set email alerts
|

Joining Technologies for Metal Additive Manufacturing in the Energy Industry

Abstract: Additive manufacturing (AM) has captured the imagination of the manufacturing community and has revolutionary potential across a number of energy applications. One particular challenge for these applications is the large size of metal AM components that are compelling to be printed. This necessitates welding and joining processes to integrate metal AM parts into larger assemblies, as well as the ability to repair and rework metal AM parts that may have defects. This work characterizes the microstructural and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…This pore-rich region is observed in the weld zone (WZ) near the fusion line in the PBF-LB parts. This critical and weak region, which has also been observed by other authors [35][36][37]39,[43][44][45]52] and affects the quality of the joint itself, will be referred to as a pore belt for future reference.…”
Section: Fusion Welding Processesmentioning
confidence: 75%
See 3 more Smart Citations
“…This pore-rich region is observed in the weld zone (WZ) near the fusion line in the PBF-LB parts. This critical and weak region, which has also been observed by other authors [35][36][37]39,[43][44][45]52] and affects the quality of the joint itself, will be referred to as a pore belt for future reference.…”
Section: Fusion Welding Processesmentioning
confidence: 75%
“…Although the formation of the pore belt region is more pronounced in arc-welded specimens [35][36][37], it has also been observed in LBW-welded specimens [39,[43][44][45] and in EBW-welded specimens [52]. Based on the reported ultimate tensile strength values of the welds made by fusion welding processes, the EBW process appears to be the most suitable for welding Al alloys produced by additive PBF-LB (Figure 18).…”
Section: Fusion Welding Processesmentioning
confidence: 96%
See 2 more Smart Citations
“…They found that gas tungsten arc welding (GTAW) and friction stir welding (FSW) are feasible joining techniques for these additively manufactured components. These methods have shown potential in providing reliable joining capabilities and preserving the integrity of the metal parts [10]. Hassanin et al investigated the joining process of additively manufactured parts made of Ti6Al4V and AlSi10Mg.…”
Section: Introductionmentioning
confidence: 99%